Adrenal steroids reference ranges in infancy determined by LC-MS/MS - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; BORAN, PERRAN; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (SPRINGERNATURE, 2022)
Background Interpretation of the results of steroid hormone measurements is challenging at early infancy. The liquid chromatography-tandem mass spectrometry (LC-MS/MS) method provides a powerful tool for diagnosing steroidogenesis disorders. We aimed to develop normative data for a 14-steroid panel and four adrenal enzyme activity indices, determined by LC-MS/MS from 3 days to 6 months of age. Methods Age- and sex-specific plasma steroid concentrations were calculated in 324 healthy full-term neonates and infants (151 females). Percentile curves were devised. Steroid ratios were evaluated as biomarkers of adrenal enzyme activities. The steroid profiles of four patients with adrenal enzyme deficiencies were included to test the diagnostic efficiency. Results Nine steroids showed age, but none showed sex specificity. The concentrations of progestins and androgens were higher at 7-14 days than at 3-7 days. After the first month, adrenal androgen concentrations decreased significantly. Adrenal enzyme activities changed towards increasing cortisol over the first 6 months. There were several-fold differences in diagnostic steroids and related adrenal enzyme activity indices between the patients and the healthy group. Conclusions The majority of adrenal steroids show age-related variations in the neonatal period and early infancy. Our data will enable accurate interpretation of steroid measurements for etiologic diagnosis of disorders of steroidogenesis. Impact LC-MS/MS method is capable of quantitating numerous analytes simultaneously, which provides an integrated picture of adrenal steroidogenesis in a small amount of sample. The development of LC-MS/MS-based normative data of steroid hormones in healthy infants is crucial to differentiate physiologic alterations from steroidogenic defects during the first 3-6 months of infancy. Previous studies had limitations due to the small numbers of samples available by sex and by age groups. Our detailed normative data and percentile curves will enable accurate interpretation of steroid measurements for etiologic diagnosis of disorders of steroidogenesis without the need for further invasive testing.
Keywords: TANDEM MASS-SPECTROMETRY; REFERENCE INTERVALS; 1ST YEAR; HYPERPLASIA; DEHYDROEPIANDROSTERONE; TESTOSTERONE; ALDOSTERONE; CATABOLISM; CHILDREN; HORMONES